Juvenile Systemic Sclerosis- A Case Report - Rahman, ASMM; Uddin, MB (TAJ: Journal of Teachers Association, 2018)
Juvenile systemic sclerosis (JSS) is a multisystem disorder as well as rare disease of childhood, and the amount of published data is limited. It appears that its clinical presentation differs from adult disease and the limited form affects only very few children. The organ involvement pattern differs also from the adult form. Prognosis seems to be better with a 5-yr survival of 95% of the JSS patients. Though the incidence is very rare but we describe a 10-yr-old boy who presented with typical features of JSS. TAJ 2016; 29(2): 70-72